2015
DOI: 10.1093/jb/mvv077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aes nuclear foci in colorectal cancer cells

Abstract: Amino-terminal enhancer of split (Aes) is a member of Groucho/Transducin-like enhancer (TLE) family. Aes is a recently found metastasis suppressor of colorectal cancer (CRC) that inhibits Notch signalling, and forms nuclear foci together with TLE1. Although some Notch-associated proteins are known to form subnuclear bodies, little is known regarding the dynamics or functions of these structures. Here, we show that Aes nuclear foci in CRC observed under an electron microscope are in a rather amorphous structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We recently found that AES suppresses invasion and metastasis of CRC through Notch signaling inhibition, and forms NM foci together with Rbpj transcription complex, TLE1, and HSC70 . It is known that transcription factor YY1 is associated with NM and nucleoli .…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that AES suppresses invasion and metastasis of CRC through Notch signaling inhibition, and forms NM foci together with Rbpj transcription complex, TLE1, and HSC70 . It is known that transcription factor YY1 is associated with NM and nucleoli .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TLEs can regulate Notch effects by triggering suppressive epigenetic modification and inhibiting HES1 target gene expression (Cuevas et al, 2005;Buscarlet et al, 2008;Espinosa et al, 2010;Larabee et al, 2013;Schnell et al, 2015;Shang et al, 2016;Zhang et al, 2019). In addition, TLE5 may recruit HDAC3 to the promoter of Notch target genes in colorectal cancer cells to suppress transcription, and interestingly, these effects depend on unique TLE complexes formed by TLE1 and TLE5 in the nucleus (Sonoshita et al, 2011;Itatani et al, 2016).…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…However, the effect of GKN2 to induce apoptosis was dependent on its interaction with Hsc70 (62). Also, Hsc70 has also been described as an important player in the mechanism regulating the suppression of colorectal cancer metastasis by its interaction with the amino-terminal enhancer of split protein (Aes) (63). Finally, it was shown that colon cancer tissues displayed increased expression and protein complexes of Hsp70, Hsp90 and HOP compared with control tissues, suggesting an association between cancer progression and complexes formation (64).…”
Section: Hsc70 Proteinmentioning
confidence: 99%